International Economics - Kenen, B.P. (New Jersey : Prentice-Hall, Inc, 1964)
The book discusses how international trade and investment affect the allocation of world resources, and how the various barriers modify that allocation. It further examines foreign trade and investment as engines of economic growth, seeking to determine how they can contribute to the development of the new nations
includes index
SJU 22/01/2019
Loans
Keywords: International economics